Prevalence and management of diabetes and associated risk factors by regions of Thailand: Third National Health Examination Survey 2004 - Wichai Aekplakorn (2018)
OBJECTIVE - The aim of this study was to determine the prevalence of diabetes and impaired fasting glucose (IFG) and their association with cardiovascular risk factors and to evaluate the management of blood glucose, blood pressure, and cholesterol in individuals with diabetes by geographical regions of Thailand. RESEARCH DESIGN AND METHODS - With the use of a stratified, multistage sampling design, data from a nationally representative sample of 37,138 individuals aged ≥ 15 years were collected using questionnaires, physical examination, and blood samples. RESULTS - The prevalence of diabetes and IFG weighted to the national 2004 population was 6.7% (6.0% in men and 7.4% in women) and 12.5% (14.7% in men and 10.4% in women), respectively. Diabetes was more common in urban than in rural men but otherwise prevalence was relatively uniform across geographical regions. In more than one-half of those with diabetes, the disease had not been previously diagnosed, although the majority of those with diabetes were treated with oral antiglycemic agents or insulin. The prevalence of associated risk factors was high among individuals with diabetes as well as those with IFG. Two-thirds of those with diabetes and concomitant high blood pressure (≥130/80 mmHg) were not aware that they had high blood pressure, and >70% of those with diabetes and concomitant high cholesterol (total cholesterol ≥6.2 mmol/l) were not aware that they had high cholesterol. CONCLUSIONS - The prevalences of diabetes and IFG were uniformly high in all regions. Improvements in prevention, diagnosis, and treatment of diabetes and associated risk factors are required if the health burden of diabetes in Thailand is to be averted. © 2007 by the American Diabetes Association.